KONFLIK POLITIK ANTAR KOALISI DALAM PEMBENTUKAN ALAT KELENGKAPAN DEWAN DI DPRD KUANTAN SINGINGI - Hidayat, Rizal D.; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The formation of the Council Equipment (AKD) cannot be separated from the strength of the political parties who form coalitions as a means to achieve common goals. The presence of these coalitions often causes conflict between coalitions which results in non-fulfillment of tasks and functions. Harold D. Lasswell said that politics matters“Who Gets What, When, How” Meanwhile, Michel E. Brown mentioned the connection between the causes of political conflict. This research aims to determine the causal factors, impacts and patterns of resolving political conflicts between coalitions in the formation of AKD in the Kuantan Singingi DPRD. Qualitative methods are used to explain descriptive data. The type of research data used is primary data from research informants and secondary data in the form of related data from related documents. The research location in this study was the Kuantan Singingi Regency DPRD. This research found that the cause of conflict in the Kuansing DPRD was due to the Sanjay Coalition's dissatisfaction with the Council Equipment (AKD) selection system in the Kuantan Singingi DPRD. This had an impact on the difficulty of reaching and making decisions at the meeting due to the absence of the Sanjay coalition so that the meeting did not reach quorum. This caused the DPRD to experience cancellation of the plenary meeting (LKPj) and a delay in the APBDP in Kuantan Singingi. The conflict resolution pattern used is mediation and filing a lawsuit with the State Administrative Court (PTUN). Keywords: Council Equipment, Conflict, Coalition, DPRD Kuantan Singingi